(untitled) (Proceedings of Faculty of Civil Engineering, 2019)
Experimental testing of the dynamic response of a simply supported beam model with discrete masses has been carried out. The range of excitation amplitudes for which the response is linear have been determined. The experimentally obtained displacements are presented for the case of harmonic uniform and non-uniform excitation, as well as for the simulation of the Northridge earthquake, which could be used as experimental benchmarks for multiple support excitation.